2012
DOI: 10.1017/jfm.2012.342
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics ofm= 0 andm= 1 modes and of streamwise vortices in a turbulent axisymmetric mixing layer

Abstract: The near field of a Reynolds number Re 0 = 2.14 × 10 5 and low-Mach-number cylindrical jet has been investigated by means of a high-speed stereo PIV setup that provides the spatio-temporal velocity field in a transverse plane, two diameters downstream of the jet exit. Proper orthogonal decomposition (POD) and spatiotemporal correlations are used to identify some of the main dynamical features of this flow. We show that the flow is dominated by streamwise vortices whose production and spatial organization can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 45 publications
6
30
0
Order By: Relevance
“…The global dynamics of round jets is known to be dominated by fluctuation modes of azimuthal wavenumbers m = 0 and m = 1, the m = 0 mode being dominant where the shear layer thickness is small with respect to the diameter (see for instance Davoust, Jacquin & Leclaire (2012)). In the present article, the investigated jet is measured rather near to the nozzle exit, and θ is approximately 0.023 near the nozzle, explaining the apparent axisymmetry of the fluctuations that can be clearly observed in the PIV snapshots (symmetric streamwise velocity field and antisymmetric cross-stream velocity field; see figure 6).…”
Section: Experimental Set-up and Data Processingmentioning
confidence: 99%
“…The global dynamics of round jets is known to be dominated by fluctuation modes of azimuthal wavenumbers m = 0 and m = 1, the m = 0 mode being dominant where the shear layer thickness is small with respect to the diameter (see for instance Davoust, Jacquin & Leclaire (2012)). In the present article, the investigated jet is measured rather near to the nozzle exit, and θ is approximately 0.023 near the nozzle, explaining the apparent axisymmetry of the fluctuations that can be clearly observed in the PIV snapshots (symmetric streamwise velocity field and antisymmetric cross-stream velocity field; see figure 6).…”
Section: Experimental Set-up and Data Processingmentioning
confidence: 99%
“…For example, manipulation of these structures can help improve combustion efficiency and reduce jet noise (Crow & Champagne 1971;Zaman 1985). This paper aims at exploring further and proving the validity of one such interaction, recently hypothesized to underlie a new shear layer spatial organization in Davoust, Jacquin & Leclaire (2012).…”
Section: Introductionmentioning
confidence: 98%
“…Jung, Gamard & George (2004), expanding the above experiment, found that the most energetic, non-zero azimuthal wavenumber scaled inversely to downstream location. Other experiments investigating streamwise vortices in high Reynolds number jets, exiting from both transitional and turbulent boundary layers, found that interactions between strong streamwise vortices and weak axisymmetric vortices may generate further streamwise vortices (Davoust, Jacquin & Leclaire 2012;Kantharaju et al 2020). As the importance of streamwise vortices to the overall dynamics became increasing apparent, various techniques such as chevrons (Bridges, Wernet & Brown 2003;Saiyed, Mikkelsen & Bridges 2003;Bridges & Brown 2004;Violato & Scarano 2011) and microjets (Arakeri et al 2003;Greska et al 2005;Alkislar, Krothapalli & Butler 2007;Yang et al 2016) were implemented to impact the near-field turbulence for far-field noise reduction.…”
Section: Introductionmentioning
confidence: 99%